Influence of Hydraulic Fracturing on Strata Behavior in Buertai Coal Mine - REN Yongqiang, NIU Tonghui (Meikuang Anquan, 2020)
In view of the multiple occurrences of dynamic disasters during the stoping of 42106 fully mechanized caving face in Buertai Coal Mine, in order to analyze the influence of hydraulic fracturing on strong pressure development, field measurement and theoretical analysis methods were adopted. Based on the mechanism of hydraulic fracturing and the theory of pressure control, the overburden strata in the return roadway of the working face were hydraulic fracturing and pressure relief. The mechanism and effect of pressure relief are analyzed in combination with the changes in the field monitoring of mine pressure. The results reveal that hydraulic fracturing under the influence of strong dynamic pressure can effectively weaken the high stress in roof strata and release the elastic energy stored in roof strata. Weaken the basic roof, avoid the rear hanging roof of goaf, and reduce the influence of leading support pressure; the influence of adjacent goaf on mining roadway of working face is reduced and surrounding rock deformation of roadway is alleviated effectively.